2012
DOI: 10.1371/journal.pone.0036494
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Ultra-Wide Genotyping Using Roche/454 Pyrosequencing for Surveillance of HIV Drug Resistance

Abstract: BackgroundGreat efforts have been made to increase accessibility of HIV antiretroviral therapy (ART) in low and middle-income countries. The threat of wide-scale emergence of drug resistance could severely hamper ART scale-up efforts. Population-based surveillance of transmitted HIV drug resistance ensures the use of appropriate first-line regimens to maximize efficacy of ART programs where drug options are limited. However, traditional HIV genotyping is extremely expensive, providing a cost barrier to wide-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 27 publications
3
73
0
1
Order By: Relevance
“…The Pyrosequencing methodology is a synthesis process, typically, a "wash-and-scan" technique, where the DNA polymerase halts between read steps and may introduce mutation errors. Furthermore, It has been shown that mutation errors in pyrosequencing reads tend to occur predominantly in homopolymeric regions (17,27). In the present study we did not assess the error rate of the present assay; however, others have estimated the overall error rate of the pyrosequencing technique to be on the average of 0.3% (12,28).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The Pyrosequencing methodology is a synthesis process, typically, a "wash-and-scan" technique, where the DNA polymerase halts between read steps and may introduce mutation errors. Furthermore, It has been shown that mutation errors in pyrosequencing reads tend to occur predominantly in homopolymeric regions (17,27). In the present study we did not assess the error rate of the present assay; however, others have estimated the overall error rate of the pyrosequencing technique to be on the average of 0.3% (12,28).…”
Section: Discussionmentioning
confidence: 69%
“…In the present study we did not assess the error rate of the present assay; however, others have estimated the overall error rate of the pyrosequencing technique to be on the average of 0.3% (12,28). It was also previously shown that the pyrosequencing error rate for detection of 17 known drug resistance mutations, located at homopolymer regions in the PR and RT genes of subtype B viruses, was Ͻ0.71% (17). Nevertheless, it was recently reported that the RT K65R mutation that is located at a homopolymer region of subtype C viruses had a pyrosequencing error rate of detection of up to 1.3% (27).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Luego se procedió a la transcripción reversa, síntesis de ADN complementario, generación de amplicones, purificación de los productos de la reacción de polimerasa en cadena (RPC), cuantificación de los productos purificados de RPC, elaboración de la librería de amplicones, RPC en emulsión, recuperación de las perlas con los productos de RPC obtenidos, cuantificación de las perlas recuperadas y la secuenciación, utilizando las especificaciones detalladas en el manual GS Junior Training (Roche) 8 y las instrucciones del fabricante (Roche) 9,10 . En 27 muestras se utilizó la versión 2.0 que permite la detección de fragmentos del gen pol que codifican para la transcriptasa reversa (TR) y la proteasa (PR) con un límite de detección de 20.000 copias/mL 11 , en el resto de las muestras (74 plasmas) se utilizó la versión 3.0 en la que además de los fragmentos anteriores se detecta el fragmento que codifica la integrasa (IN) y posee un límite de detección de 2.000 copias/mL 12 .…”
Section: Experimentos Realizadosunclassified